Factores de riesgo que inciden en la hipertensión arterial en mujeres embarazadas atendidas en el Hospital Martin Icaza de Babahoyo en el primer semestre del 2018 - Holguín Ortega, Maricela Elizabeth (2018)
Hypertension in pregnancy is one of the most frequent complications that cause maternal-fetal morbidity and mortality, so the reduction of its incidence is a priority. The research method used in the present research study is the deductive method, it is a scientific method that starts from the general (laws or principles) to the particular (phenomena or concrete facts), through a reflective, synthetic and analytical process, that is to say which part of the problem to determine its possible causes, with a sample of 60 pregnant women who attended the Martin Icaza hospital in the city of Babahoyo-Province of Los Ríos. In this way, the tabulation and analysis of the data was carried out, relating the problem to its possible causes. The main objective of this research study is: To establish the risk factors that affect arterial hypertension in pregnant women treated at the Martin Icaza de Babahoyo Hospital in the first semester of 2018. We conclude this research study stating that biological risk factors such as age, race, family history, personal history, malnutrition and the presence of chronic diseases are those that mainly affect high blood pressure in pregnant women treated at the Martin Hospital Icaza de Babahoyo in the first semester of 2018, that the incidence of hypertension in pregnant women treated at the Martin Icaza Hospital in Babahoyo in the first semester of 2018, is high, since 67% of cases of hypertension in pregnant women were new cases.